Analysis of the determinants of regional financial independence in West Nusa Tenggara Province in 2019-2024: Analisis determinan kemandirian keuangan daerah di Provinsi Nusa Tenggara Barat tahun 2019-2024 - Septini, Ni Nengah; Suriadi, Irwan (Academia Open, 2026)
General Background Regional fiscal independence reflects the capacity of local governments to finance expenditures without excessive reliance on central transfers, constituting a key dimension of fiscal decentralization. Specific Background In the observed period, regional finance is predominantly supported by transfer revenue, indicating persistent dependency and uneven fiscal capacity across administrative units. Knowledge Gap Prior studies tend to examine fiscal variables in isolation, leaving limited integrative evidence on how local revenue, transfers, capital expenditure, economic growth, and financial effectiveness jointly relate to fiscal independence. Aims This study analyzes the determinants of regional fiscal independence using panel data and a comprehensive framework incorporating multiple fiscal and economic indicators. Results Empirical findings reveal that local own-source revenue shows a significant positive relationship with fiscal independence, while transfer revenue demonstrates a significant negative relationship, indicating a flypaper effect. In contrast, capital expenditure, economic growth, and financial effectiveness do not show significant partial relationships, although all variables jointly exhibit statistical significance. Novelty The study advances an integrative analytical approach by combining fiscal structure, economic performance, and governance dimensions within a single empirical model. Implications Strengthening local revenue through diversification and digitalization, alongside more productive use of transfers and improved governance quality, is essential for advancing sustainable fiscal independence. HIGHLIGHTS• Local revenue shows consistent statistical significance in explaining fiscal capacity• Transfer funds correlate inversely with autonomy, indicating resource dependency patterns• Combined fiscal variables demonstrate strong explanatory power within panel estimation KeywordsRegional Financial Independence; Local Revenue; Transfer Revenue; Capital Expenditure; Economic Growth